THE POTENTIAL OF ADJUVANT AGAINST PRODUCTION OF ANTISTREPTOCOCCAL IMMUNOGLOBULIN Y (IGY) IN AQUACULTURE - Rizkiantino, Rifky; Wibawan, I Wayan Teguh; Pasaribu, Fachriyan Hasmi; Soejoedono, Retno Damajanti; Poetri, Okti Nadia; Arnafia, Wyanda; Sasi, Kris Damar; Reisinta, Dinda (Universitas Syiah Kuala, 2020)
This study was conducted to explore the potential of adjuvant for the production of immunoglobulin Y (IgY) as antistreptococcosis in layer chicken with mass production orientation. Enterococcus faecalis which causes streptococcosis in the red tilapia was selected as a candidateantigen. The production of immunoglobulin Y (IgY) was carried out on Isa Brown layer chickens and aged around 20 weeks. Furthermore, thechickens were grouped into four groups (A, B, C, and D groups), each consisting of three chickens based on the type of adjuvant, while twochickens were used as a control group. Each group was treated by giving MONTANIDE ISA 71R VG adjuvant (A), Freund's adjuvant (B), aluminum potassium sulphate adjuvant (KAl(SO4)212H2O) concentration of 50 ppm in pH 7 (C), and only antigens without adjuvant (D). Chickens were kept for 35 days and each week was checked for presence the IgY antigen in the serum and egg yolk. Booster was conducted on 14th and 28th days of maintenance. The results showed that IgY in treatment group A was detected on day 28 in the serum and day 35 in the yolk. Whereas the treatment group B could be detected on day 35 in the serum. However, the IgY was not detected in the serum and yolk in C, D, and control groups until the end of the maintenance. Based on the results, it can be concluded that the appearance of IgY in serum and yolk in a relatively fast time is obtained in the combination of Enterococcus faecalis antigen with the emulsion of water-in-oil adjuvant (SEPPICMONTANIDE ISA 71R VG) compared to the other types of adjuvant that use in this study.